Electrochemical, photovoltaic and DFT studies on hybrid materials based on supramolecular self-assembly of a ditopic twisted perylene diimide with square-planar platinum(II)- and/or palladium(II)-2,2′:6′,2-terpyridyl complex ions - Buyukeksi, Sebile Isik; Orman, Efe Baturhan; Acar, Nursel; Altindal, Ahmet; Ozkaya, Ali Riza; Sengul, Abdurrahman (ELSEVIER SCI LTD, 2019)
A ditopic bridging ligand, N,N'-bis(pyridine)-1,6,7,12-tetrakis-(4-methoxyphenoxy)perylene diimide (1) was synthesized. Metallosupramolecular self-assembly of 1 with 2,2':6',2 ''-terpyridyl-platinum(II) and/or -palladium (II) complex ions afforded to new triads [(terpy)M(II)-(1)-M(II)(terpy)1(NO3)(4) where, M(II) = Pt(II) (2), and Pd (II) (3), respectively. These isolated triads 2 and 3 and also free ligand 1 were fully characterized by FT-IR, H-1 NMR, C-13 DEPT NMR, H-1-H-1 COSY NMR, MALDI TOF and HRMS (MALDI-TOF/TOF-MS) mass techniques and UV/Vis spectroscopy. DFT studies revealed that the molecular structure of 1 is highly distorted and deviated from the planarity by bulky methoxyphenyl groups at bay positions. The calculated HOMO and LUMO are located on the PDI core and phenyl groups, and the band gap was found to be 2.27, 2.23 and 2.24 eV in DMSO for 1, 2 and 3, respectively. The calculated UV/Vis spectra are in good agreement with those of experimental results. Electrochemical, in situ spectroelectrochemical and in situ electrocolorimetric measurements in solution suggested that redox processes of the compounds are accompanied by favourable electron transport properties with remarkably narrow HOMO-LUMO gaps and intense light absorption over the visible range. The association of usually reversible and fast electron transfer processes with the net colour changes in solution pointed out the applicability of the compounds as an electrochromic material. The electrochromic performance measurements with the films of the compounds on indium tin oxide glass provided additional support for their usability as a colour changing material in electrochromic devices. Surface morphologies of the films were characterized by scanning electron microscopy (SEM). The metal complexes of 1, especially the platinum(II) complex (2), behaved as a good neutral and cathodic colouring electrochromic material with fast response time, long-term stability, and long-term write erase efficiency. The photovoltaic performance of the compounds as electron acceptor material was investigated by varying their relative ratio in the bulk heterojunction solar cells. It was found that the photovoltaic conversion efficiency of the devices strongly depends on the blend ratio. The optimized performance for the devices was obtained with the P3HT:PDIs (weight ratio 1.0:1.5) blended films. For this blend ratio, the device showed a maximum conversion efficiency of 3.91%, 8.17% and 5.18% for 1, 2 and 3, respectively. The results obtained reveal that employing 2 as an acceptor material has great potential for the development of highly efficient nonfullerene bulk heterojunction photovoltaic devices.
Keywords: Perylene diimide (PDI); Pyridine; Terpyridine; Square-planar complexes; Photovoltaics; Density functional theory; EFFECTIVE CORE POTENTIALS; OPEN-CIRCUIT VOLTAGE; ORGANIC SOLAR-CELLS; MOLECULAR CALCULATIONS; HIGH-PERFORMANCE; MORPHOLOGY; PHTHALOCYANINES; NETWORK; Chemistry; Engineering; Materials Science